An MDA Framework Supporting OCL - Brucker, Achim; Doser, Jürgen; Wolff, Burkhart (Electronic Communications of the EASST, 2007)
We present a model-driven architecture (MDA) framework that integrates formal analysis techniques into an industrial software development process model. This comprises modeling using UML/OCL, processing models by model transformations, code generation (including runtime-test environments) and formal analysis using the theorem proving environment HOL-OCL. Moreover, our frameworks supports the verification of proof obligations that are generated during model transformations. We show the extensibility of our approach by providing a SecureUML extension of the framework, which allows for an integrated specification of security properties, their analysis and their conversion to code.